An evaluation of service quality from visitors' perspectives: The case of Niah National Park in Sarawak - Abas, Said; Ahmad, Shuib; Norazirah, Ayob; Fazlina, Yaakub (Universiti Malaysia Sarawak, 2013)
This study assessed the quality of services in Niah National Park (NNP) located in Sarawak, a major ecotourism destination in Malaysia. The ECOSERV instrument developed by Khan in 2003 was modified to measure visitors' expectations and perceptions on services quality. Self-administered questionnaires were handed out to registered park visitors and collected back upon completion. The findings had revealed negative service gaps (differences between visitors' perceptions and expectations) pattern in almost all sixteen attributes and all six dimensions of services. This indicated that the levels of service quality in NNP are not meeting visitors' expectations, especially on the dimension of ecotangibles. In order to enhance visitors' satisfaction, there is a need to address deficiency in the quality of services in the NNP. This is to avoid a decline in competitive advantage of NNP as an ecotourism attraction and not to hamper visitors' experience and also to ensure continuous support to conserve the park's rich biodiversity and natural resources.